The Effectiveness Of Entrepreneurial Development Mechanism Implemented By Bank Pembangunan Infrastruktur Malaysia Berhad (BPIMB) Towards Bpimb Factory Scheme’s (BFS) Participant - MOHAMAD HUSSAIN, MAZDHEE (2005)
This research was conducted to investigate the effectiveness level of entrepreneurial development mechanism implemented by Bank Pembangunan & Infrastruktur Malaysia Berhad (BPIMB) towards BPIMB Factory Scheme’s (BFS) participants throughout Malaysia. The purpose of this research is to determine whether independent variables, financial services (financing processing period and financial facilities characteristics) and non-financial services (advisory services, entrepreneurial development programs, factory building’s characteristics, incubator services and flexible factory rental terms) plays an important role in influencing dependent variable BFS participant’s business performance (profitability and sales and internal growth).